Anti-plasmodial Activity of Chloroform Leaf Extract of Eucalyptus camaldulensis in Mice (African Journal of Biomedical Research, 2019)
Malaria outbreak has been a case of concern for quite a long time now. With the ever increasing resistance to the available standard antimalarial drugs, there is need for the development of new antimalarial drugs, hence, the purpose of this research is to evaluate the antiplasmodial activity of the chloroform leaf extract of Eucalyptus camaldulensis at various dosage concentrations in vivo compared to chloroquine treatment in experimental mice infected with chloroquine sensitive Plasmodium berghei NK65 strain. Groups A, B and C mice were infected and treated with 100, 200 and 300 mg extract/kg body weight of mouse respectively while group D was infected and treated with 25mg chloroquine /kg body weight, group E was infected but not treated and group E was unfected, untreated. The phytochemical constituents of the plant extract were evaluated giving 8 phytochemicals including flavonoids. In addition, the extract indicated a dose dependent decrease in the level of parasitaemia. The analysis showed that the extract has no effect on the packed cell volume of the experimental mice. Also, some of the groups lived 10 days beyond the experimental period. Furthermore, the body weights of the groups treated with 100mg/kg and 300mg/kg extract reduced compared to the infected untreated group whereas, the groups treated with 200mg/kg extract, 25mg/kg chloroquine and uninfected untreated increased in body weight compared to the negative control (infected untreated). Therefore, the chloroform leaf extract of Eucalyptus camaldulensis could serve as a possible source of antimalarial compounds.
Keywords: Plasmodium berghei; malaria; Eucalyptus camaldulensis; antiplasmodial; chloroform extract